ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH KREATIF SD MUHAMMADIYAH 16 SURABAYA DALAM MEMBANGUN LINGKUNGAN BELAJAR YANG INKLUSIF DAN ADAPTIF - Sati; Syahril Shobirin; Siti Fatimah; ⁠Putri Andini; Muhammad Fadli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Differentiated learning is an instructional approach that tailors the learning process to students' needs and abilities to create an inclusive environment. This study discusses the implementation of differentiated learning at Sekolah Kreatif SD Muhammadiyah 16 Surabaya, covering aspects of content, process, and product to support students' academic and social development, including those with special needs. The objective of this research is to analyze the implementation of differentiated learning, as well as the supporting factors and challenges faced in its application. This study employs a descriptive qualitative method with data collection techniques including observation, interviews with teachers and students, and school document analysis. Data were obtained from observations and interviews regarding the implementation of differentiated learning. The findings indicate that Sekolah Kreatif SD Muhammadiyah 16 Surabaya applies team teaching, project-based learning, and the use of technology in the learning process. Teachers adapt their teaching methods to match students' learning styles, while support from parents and collaboration with external partners such as therapy institutions and healthcare agencies further enhance inclusive learning. In conclusion, differentiated learning at Sekolah Kreatif SD Muhammadiyah 16 Surabaya has been implemented effectively, although challenges such as limited supporting teachers and the need for more adaptive strategies remain. Continuous improvements are being made through teacher training, enhanced collaboration, and parent outreach. With a continuously evolving approach, this school can serve as a model for other institutions in implementing inclusive and effective education.